1978
DOI: 10.1126/science.201.4362.1244
|View full text |Cite
|
Sign up to set email alerts
|

Tree Ring Evidence for Chronic Insect Suppression of Productivity in Subalpine Eucalyptus

Abstract: Experimental reduction of insect grazing pressures suggests that longterm, continuous feeding by phytophagous insects has severely depressed growth and productivity of subalpine Eucalyptus trees (measured by annual ring growth) for at least 25 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
81
2
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(86 citation statements)
references
References 12 publications
1
81
2
1
Order By: Relevance
“…Consequently the trees selected for climate reconstruction may include both an herbivore signal as well as a climate signal. Although some authors have suggested herbivory may make trees unsuitable for climate reconstruction (5,7), the interactions of these factors, to our knowledge, have not been assessed, and the importance of this potential interaction is furthered by the fact that herbivory (or lack thereof) is not currently a part of the field criteria for selecting wood samples used for the reconstruction of climate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently the trees selected for climate reconstruction may include both an herbivore signal as well as a climate signal. Although some authors have suggested herbivory may make trees unsuitable for climate reconstruction (5,7), the interactions of these factors, to our knowledge, have not been assessed, and the importance of this potential interaction is furthered by the fact that herbivory (or lack thereof) is not currently a part of the field criteria for selecting wood samples used for the reconstruction of climate.…”
mentioning
confidence: 99%
“…Reconstructions of biotic factors, specifically herbivory, have largely been dependent on using observational data to infer the herbivore signal (usually manifest as reduced ring width) within the tree ring record (but see ref. 5). Of the observational methods developed for reconstructing herbivore outbreaks, there are two strategies commonly used (3,6,7).…”
mentioning
confidence: 99%
“…Herbivory in both marine and terrestrial conlmunities can be very intense, reducing the growth and s u~v a l of individual plants and influencing interspecific competition and community structure (Rockwood 1973, Vadas 1977, Lubchenco 1978, Morrow & LaMarch 1978, Ogden & Lobe1 1978, Rausher & Feeny 1980, Hay 1981b,c, Lubchenco & Gaines 1981, Gaines & Lubchenco 1982, Coley 1983). The importance of plant defensive mechanisms, especially the role of secondary metabolites as chemical defenses against herbivores, has been recognized and studied extensively in terrestnal communities (Fraenkel 1959, Sondheimer & Simeone 1970, Whittaker & Feeny 1971, Levin 1976, Harborne 1977, Rosenthal & Janzen 1979.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variation for resistance to insect attack has been documented in many natural plant populations (Berenbaum et aI., 1986;Fritz et aI., 1987;Karban, 1987;Maddox and Root, 1987;Rausher and Simms, 1989), and herbivory is generally thought to be detrimental to plant fitness (Mattson and Addy, 1975;Morrow and LaMarche, 1978;Janzen, 1979;Rausher and Feeny, 1980;Marquis, 1984;Sacchi et aI., 1988; but see Paige and Whitham, 1987;Maschinski and Whitham, 1989). These two observations suggest that insects may impose natural selection on their host plants (e.g., Rausher and Simms, 1989).…”
mentioning
confidence: 99%